A compact reconfigurable aperture coupled fed antenna for intelligent transportation system application. Issue 7 (10th March 2020) - Tripathi, Shivesh; Pathak, Nagendra P.; Parida, Manoranjan
Abstract: This article presents a novel reconfigurable aperture coupled fed antenna with a defected ground plane for an intelligent transportation system (ITS). The antenna design with aperture coupled feed line. The defected ground plane allows variation in reactance of the proposed antenna around the center frequency and coupling of energy. This antenna is multiband and works at resonant frequencies of 2.45, 5.9, and 24 GHz allowing measurable reconfigurability with the help of PIN diode. From the measurement, one can infer that the bandwidth is 0.8, 1, and 8.5 GHz, and gain obtained are 11.7, 4.04, and 4.4 dBi at 2.45, 5.9, and 24 GHz frequencies, respectively. It is circularly polarized with a broadside radiation pattern. The advantage of this design is that it covers all the three bands allocated by the Federal Communications Commission for ITS and vehicular communication applications. It is an electrically small, low profile antenna and has a simple structure thus gives large bandwidth.